Evidence for the Effect of Vaccination on Host-Pathogen Interactions in a Murine Model of Pulmonary Tuberculosis by Mycobacterium tuberculosis - Zatarain-Barrón, Zyanya Lucia; Ramos-Espinosa, Octavio; Marquina-Castillo, Brenda; Barrios-Payán, Jorge; Cornejo-Granados, Fernanda; Maya-Lucas, Otoniel; López-Leal, Gamaliel; Molina-Romero, Camilo; Anthony, Richard M.; Ochoa-Leyva, Adrián; De La Rosa-Velázquez, Inti Alberto; Rebollar-Vega, Rosa Gloria; et al. (Frontiers in Immunology, 2020)
The global control of Tuberculosis remains elusive, and Bacillus Calmette-Guérin (BCG) -the most widely used vaccine in history- has proven insufficient for reversing this epidemic. Several authors have suggested that the mass presence of vaccinated hosts might have affected the Mycobacterium Tuberculosis (MTB) population structure, and this could in turn be reflected in a prevalence of strains with higher ability to circumvent BCG-induced immunity, such as the recent Beijing genotype. The effect of vaccination on vaccine-escape variants has been well documented in several bacterial pathogens; however the effect of the interaction between MTB strains and vaccinated hosts has never been previously described. In this study we show for the first time the interaction between MTB Beijing-genotype strains and BCG-vaccinated hosts. Using a well-controlled murine model of progressive pulmonary-tuberculosis, we vaccinated BALB/c mice with two different sub-strains of BCG (BCG-Phipps and BCG-Vietnam). Following vaccination, the mice were infected with either one of three selected MTB strains. Strains were selected based on lineage, and included two Beijing-family clinical isolates (strains 46 and 48) and a well characterized laboratory strain (H37Rv). Two months after infection, mice were euthanized and the bacteria extracted from their lungs. We characterized the genomic composite of the bacteria before and after exposure to vaccinated hosts, and also characterized the local response to the bacteria by sequencing the lung transcriptome in animals during the infection. Results from this study show that the interaction within the lungs of the vaccinated hosts results in the selection of higher-virulence bacteria, specifically for the Beijing genotype strains 46 and 48. After exposure to the BCG-induced immune response, strains 46 and 48 acquire genomic mutations associated with several virulence factors. As a result, the bacteria collected from these vaccinated hosts have an increased ability for immune evasion, as shown in both the host transcriptome and the histopathology studies, and replicates far more efficiently compared to bacteria collected from unvaccinated hosts or to the original-stock strain. Further research is warranted to ascertain the pathways associated with the genomic alterations. However, our results highlight novel host-pathogen interactions induced by exposure of MTB to BCG vaccinated hosts.